The epistemology of the concept of civil society in the West and Iranian interpretations. - Zoeram, Vahid Amani; Jawan, Jayum; Lee, Yok Fee (Canadian Academy of Oriental and Occidental Culture, 2010)

(untitled)
The article in first part is going to review the conceptual evolution of the civil society in the western political thought. It shows how the changes of dominant discourses in political thought and social transition in the west led to change of the interpretations of civil society. In second part the article illustrates Iranian scholars’ interpretations on the concept of civil society in Khatami’s era. Eventually the article concludes that common sense of civil society in Iran was affected by associational theories on civil society particularly Habermas’s public sphere notion and Cohen and Arato’s definition on the concept.